Melting of Peridotites through to Granites: A Simple Thermodynamic Model in the System KNCFMASHTOCr. (16th May 2018) - Holland, Tim J B; Green, Eleanor C R; Powell, Roger
ABSTRACT: A new set of thermodynamic models is presented for calculating phase relations in bulk compositions extending from peridotite to granite, from 0·001 to 70 kbar and from 650°C to peridotite liquidus temperatures, in the system K2 O–Na2 O–CaO–FeO–MgO–Al2 O3 –SiO2 –H2 O–TiO2 –Fe2 O3 –Cr2 O3 (KNCFMASHTOCr). The models may be used to calculate phase equilibria in partial melting of a large range of mantle and crustal compositions. They provide a good fit to experimental phase relation topologies and melt compositions across the compositional range of the model. Compared with the preliminary model of Jennings, E. S. & Holland, T. J. B. (2015) (A simple thermodynamic model for melting of peridotite in the system NCFMASOCr. Journal of Petrology 56, 869–892) for peridotite–basalt melting relations, the inclusion of K2 O and TiO2 allows for better modelling of small melt fractions in peridotite melting, and in reproducing rutile-bearing eclogite melting at high pressures. An improved order–disorder model for spinel is now incorporated. Above 10 kbar pressure, wet partial melting relations may be significantly affected by the dissolution of silicates in aqueous fluid, so the set of models includes an aqueous low-density silicate-bearing fluid in addition to a high-density H2 O-bearing silicate melt. Oxygen fugacity may be readily calculated for the whole range of bulk compositions investigated, and the effect of water content on melt f O2 is assessed.